2021
DOI: 10.1111/os.12947
|View full text |Cite
|
Sign up to set email alerts
|

One Approach Anterior Decompression and Fixation with Posterior Unilateral Pedicle Screw Fixation for Thoracolumbar Osteoporotic Vertebral Compression Fractures

Abstract: Objective The objective of the present paper was to explore the clinical effect of one approach anterior decompression and fixation with posterior unilateral pedicle screw fixation for thoracolumbar osteoporosis vertebral compression fractures (OVCF). Methods This is a single‐center retrospective analysis. A total of six thoracolumbar OVCF patients (four women and two men) with an average age of 65.2 years (58–72 years) who were treated between June 2016 and May 2018 were enrolled in the present study. The les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…If there is a significant lateral bending rotation movement with the participation of torque, the possibility of internal fixation failure is high. [49] Although this difference in stress does not have a decisive impact on the operation, the long-term stress concentration will lead to fracture of pedicle screws due to fatigue, which will bring a series of potential risks after the operation, which is not conducive to the stability of the entire internal fixation system. [50,51] The intervertebral disc is an important load center and buffer structure for spinal function.…”
Section: Discussionmentioning
confidence: 99%
“…If there is a significant lateral bending rotation movement with the participation of torque, the possibility of internal fixation failure is high. [49] Although this difference in stress does not have a decisive impact on the operation, the long-term stress concentration will lead to fracture of pedicle screws due to fatigue, which will bring a series of potential risks after the operation, which is not conducive to the stability of the entire internal fixation system. [50,51] The intervertebral disc is an important load center and buffer structure for spinal function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when there is severe vertebral body comminution or collapse, large fracture fragments may extend into the spinal canal and cause compression of the spinal cord. Treating injuries above the L1 level also carries a higher risk because of the proximity to the spinal cord 17 . Additionally, inadequate anterior support after a posterior distractive reduction for severe collapsed vertebral body may lead to correction failure or implant failure 17 .…”
Section: Posterior Surgery Of Ovcfmentioning
confidence: 99%
“…Treating injuries above the L1 level also carries a higher risk because of the proximity to the spinal cord 17 . Additionally, inadequate anterior support after a posterior distractive reduction for severe collapsed vertebral body may lead to correction failure or implant failure 17 . Watanabe et al 12 concluded that, according to the concept of load bearing and load sharing, posterior vertebral fusions can generate posterior stresses through flexion moments in standing or sitting positions, leading to a higher risk of internal fixation failure because of lack of anterior support, and thus longer segmental internal fixation fusions are required.…”
Section: Posterior Surgery Of Ovcfmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated stretching is required during the operation, so the patient will experience muscle ischemic necrosis and a degree of pain in the patient. Obviously, postoperative complications are prone to occur [ 5 ]. In recent years, various minimally invasive techniques have developed rapidly.…”
Section: Introductionmentioning
confidence: 99%